2014
DOI: 10.1177/1086296x14551474
|View full text |Cite
|
Sign up to set email alerts
|

Paucity and Disparity in Kindergarten Oral Vocabulary Instruction

Abstract: The purpose of this study was to examine how oral vocabulary instruction was enacted in kindergarten. Four days (12 hours) of instruction were observed in 55 classrooms in a range of socio-economic status schools. All instruction was coded for evidence of vocabulary instruction for a total of 660 hours of observation. Results revealed that teachers explained word meanings during "teachable moments" in the context of other instruction. Findings revealed one-time, brief word explanations, unsystematic word selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 56 publications
7
64
0
2
Order By: Relevance
“…Therefore, it is not surprising that even a small amount of information about the meaning of unfamiliar words in a text-and particularly about the specific meanings intended in the text-might give students a boost in their comprehension of a text containing the taught words. In light of this finding, it is particularly concerning that studies have repeatedly documented little vocabulary instruction in schools (Carlisle, Kelcey, & Berebitsky, 2013;Scott, Jamieson-Noel, & Asselin, 2003;Wright & Neuman, 2014).…”
Section: Theme 1: Teaching Word Meanings Supports Text Comprehensionmentioning
confidence: 99%
“…Therefore, it is not surprising that even a small amount of information about the meaning of unfamiliar words in a text-and particularly about the specific meanings intended in the text-might give students a boost in their comprehension of a text containing the taught words. In light of this finding, it is particularly concerning that studies have repeatedly documented little vocabulary instruction in schools (Carlisle, Kelcey, & Berebitsky, 2013;Scott, Jamieson-Noel, & Asselin, 2003;Wright & Neuman, 2014).…”
Section: Theme 1: Teaching Word Meanings Supports Text Comprehensionmentioning
confidence: 99%
“…Although U.S. preschool teachers have been found to use relatively richer language, ask more cognitively challenging questions, and use more decontextualized language during book reading, there appears to be limited and inconsistent explicit attention to vocabulary in both preschool and kindergarten classrooms (Al Otaiba et al., ; Dickinson, Hofer, Barnes, & Grifenhagen, ; Gerde & Powell, ; Gest et al., ; Hindman, Wasik, & Erhart, ; Massey, Pence, Justice, & Bowles, ). In one study of a socioeconomically diverse sample of 55 kindergartens, only eight episodes of vocabulary instruction occurred per day, on average, and these did not focus on sophisticated words (Wright & Neuman, ). Another statewide sample of 81 early childhood classrooms saw less than 30 seconds focused on vocabulary during 20 minutes of language and literacy instruction, on average (Pelatti, Piasta, Justice, & O'Connell, ).…”
Section: Vocabulary Support In the Chilean Classroom Contextmentioning
confidence: 99%
“…Yet, studies demonstrate that both oral language and content area learning are neglected areas of focus in the early years of schooling. Confirming U.S. national data (e.g., Blank, 2012), a recent observational study found that students received, on average, only 2.3 minutes per day of science in their kindergarten classrooms (Wright & Neuman, 2014). Likewise, studies have demonstrated that students rarely receive high-quality oral vocabulary instruction in the early primary grades (Carlisle, Kelcey, & Berebitsky, 2013;Wright & Neuman, 2014).…”
Section: Supporting Disciplinary Talk From the Start Of School: Teachmentioning
confidence: 87%